Hepatocellular carcinoma in elderly: Clinical characteristics, treatments and outcomes compared with younger adults. - Hui Guo; Tao Wu; Qiang Lu; Jian Dong; Yi-Fan Ren; Ke-Jun Nan; Yi Lv; Xu-Feng Zhang (PLoS ONE)
The number of elderly patients diagnosed with hepatocellular carcinoma (HCC) is expected to increase. The present study aims to evaluate the role of age on treatments and outcome of HCC patients. 1530 patients firstly diagnosed with HCC were retrospectively included and classified as older (≥65 years, n = 318, 21%) and younger patients (<65 years, n = 1212, 79%). The two groups were compared with clinical characteristics, tumor burden, Barcelona Clinics Liver Cancer (BCLC) stage, treatments and long-term prognosis. Elderly patients were more HCV infected, had more diabetes, poorer performance status, and were less aggressively treated. The proportion of HCC within BCLC stage 0-A, B or C was similar between the two groups, but elderly patients were more presented with BCLC stage D. The overall survival of older patients was poorer compared to younger patients before and after propensity score matching. However, elderly patients were less often effectively treated with surgery and loco-regional therapies across different BCLC stages. After stratified by BCLC stages or treatments, older patients showed comparable long-term outcome to younger patients. Performance status, BCLC stages and effective treatments, rather than age, was independent factors determining prognosis in the whole cohort and only elderly patients by multivariate analysis. In conclusion, older could have comparable survival to younger patients within the same tumor stage or after similar treatments. Thus, equally active treatments should be encouraged to elderly patients.